Hubungan Antara Faktor Penghambat Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) dengan Pelaksanaan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3): The Relationship Between Inhibiting Factors of the Occupational Safety and Health Management System (SMK3) and Its Implementation - Rachman, Rizaldy Fathur; Kunnati; Roni Iryadi (MPI Press, 2024)
Introduction: The Occupational Safety and Health Management System (SMK3) is a factor that plays an important role in hospital services. With the SMK3, it is hoped that the hospital will carry out health and safety efforts that can control and minimize potential hazards that may arise and threaten the lives and lives of hospital employees, patients and visitors in the hospital environment. However, until now the implementation of SMK3 in hospitals has often not been implemented properly. This is because there are various inhibiting factors that interfere with the smooth implementation of the RS SMK3 program Objectives: This research was conducted to determine the relationship between inhibiting factors and the implementation of SMK3 at the Gunung Jati Regional General Hospital, Cirebon City, by looking at the significant value Method: This research was conducted with a cross sectional design. Respondents in this study were 70 employees taken by stratified random sampling technique. More in-depth information about the variables studied was obtained through a questionnaire Result: The independent variable of this research is the inhibiting factor while the dependent variable of this research is the implementation of SMK3. The Somers' D correlation test shows that there is a relationship between the inhibiting factors and the implementation of SMK3 (p = 0.0001). Conclution: The conclusion that can be drawn is that there is a relationship between the inhibiting factors and the implementation of SMK3 at Gunung Jati Hospital, Cirebon Regency.